The adoption of QR codes and mobile wallets technologies by South African consumers - Malokotsi, Nomalanga (University of the Witwatersrand, Johannesburg, 2024)
The premise of this study is to contribute to the literature on the adoption of mobile payments within a South Africa context. The study focuses on QR codes and mobile wallets payment channels. These payment channels are part of the technology disruption which aims to improve efficiency, effectiveness, safety and reduce transaction costs. The research problem investigated is the low adoption rates of QR codes and mobile wallets which according to literature provides benefits to financial customers. The study sample population focuses on adults aged between 18 and 60 years old and living in different provinces of South Africa. Quantitative analysis is used to analyze a questionnaire that was completed by 178 participants. SPSS version 28.0 was used to for analyzing descriptive and inferential statistics. Parametric and non-parametric models were used in the investigation. The TAM model was used in informing the conceptual framework of this research. The results of from this study revealed that the adoption of QR codes and mobile wallets is influenced by transaction security, subjective norms, ease of use and behavior. The behavior element was tested using nudging and the study indicated that attributes of nudging such as incentives, education, knowledge, regulation have an influence of the adoption rates. The highest correlation has been the adoption of mobile payments and incentives which is a nudging attribute. It is also noted that the QR code and mobile wallets do not have the same effects on the adoption rates. This study will contribute to the South African payments sector in policy enhancements, effectiveness of marketing methods and the increase in uptake
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: QR codes; mobile wallet; mobile payments; SDG-9: Industry, innovation and infrastructure